IMPLEMENTASI KURIKULUM PENDIDIKAN ISLAM MELALUI PEMBIASAAN ADAB MAKAN DAN MASUK KAMAR MANDI MEMBENTUK AKHLAKUL KARIMAH ANAK - Aziz, Mursal; Siregar, Tarmiji; Herlisa, Herlisa (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
abstrack This study aims to analyze the implementation of the Islamic Education curriculum through the habit of table manners and toilet manners in shaping the morals of early childhood at RA Al-Arifin Rahuning. The study used a qualitative approach with a descriptive type through data collection techniques in the form of interviews, observations, and documentation of the principal, teachers, and parents. The results of the study indicate that the curriculum planning has integrated Islamic values ​​into children's daily activities, while the implementation of learning is carried out through the methods of habituation, role models, coercion, and fun activities. Evaluation was carried out authentically by observing children's behavior directly, which showed positive changes such as increased discipline, cleanliness, and awareness in implementing manners. The discussion shows that the success of this implementation is due to the consistency of habituation, the role of teachers as role models, and the support of the school and family environment, so that moral values ​​are more easily internalized by children. This study concludes that habituation based on daily activities is effective in shaping the morals of early childhood and contributes to the development of an applicable and sustainable Islamic education model.